MODELING THE PROFITABILITY OF TELECOMMUNICATION SUB-SECTOR STOCKS USING PANEL DATA REGRESSION ANALYSIS - Ni Putu Nanik Hendayanti; Maulida Nurhidayati (Jurusan Matematika FMIPA Universitas Andalas Padang, 2022)
The Covid-19 outbreak in Indonesia has wreaked havoc on the financial market, causing turbulence in the stock market. One industry that did not endure instability was the telecommunications subsector due to government initiatives connected to online learning and office tasks performed on a Work From Home (WFH) basis, which increased internet usage during online learning and WFH. Online learning and office activities carried out on a Work From Home (WFH) basis have increased the sector's profitability and breathed new life into the world of stock investment. When purchasing stocks, an investor always seeks to generate a profit. The profitability ratio reveals the profitability of the business. Profitability and investment decisions are linked as a result of a budget plan and profit forecast. This study aims to model telecommunications subsector companies' profitability on the Indonesian stock exchange using panel data regression analysis. The panel data regression analysis mixes cross-section data and time series data in which the same cross-section unit is sampled at various times. Therefore, investors must be aware of the profitability of the subsector of the telecommunications industry to make an investment decision. This research will generate a model of the profitability of subsector enterprises in the telecommunications industry. Based on the R square value of 0.8752, the results of this study indicate that ln equity, inflation, CR, and DER can explain 87.52% of the variation in ROA. In comparison, the remaining 12.48% is impacted by factors not included in the model.